Les unitariens et le pouvoir princier en Transylvanie (années 1560-années 1630) - Harai, Dénes (Renaissance and reformation, 2023)
John Sigismund Szapolyai, also known as John II, who was elected King of Hungary and later become the first Prince of Transylvania (1570-71), was heavily influenced in the last years of his life by the two Unitarian thinkers Giorgio Biandrata and Ferenc Dávid. In 1571, Unitarianism even became the fourth religion to enjoy full civil rights in Transylvania, which meant it was considered equal to Catholicism, Lutheranism, and Calvinism in the eyes of the law. Although John II's successors were all Catholic in the last three decades of the sixteenth century and Calvinist in the seventeenth, the Unitarians flourished up until the 1580s and held great influence in the country until the 1630s. This article assesses the involvement of this community in the political and diplomatic life of Renaissance Transylvania, in order to understand the representations and perceptions of the Unitarians in relation to monarchical power along the frontier between Christendom and the Ottoman Empire during the Wars of Religion.